Changes in renal function and predictors affecting renal outcome of living kidney donors: a nationwide prospective cohort study. Issue 6 (15th April 2021) - Kim, Yunmi; Kim, Min Ji; Lee, Yu Ho; Lee, Jung Pyo; Lee, Jeong‐Hoon; Yang, Jaeseok; Kim, Myoung Soo; Kim, Taehee; Kang, Sun Woo; Kim, Yeong Hoon; ,
Abstract: Aim: The safety of donors is an important issue in living donor kidney transplantation. We investigated serial changes in renal function and predictors affecting the renal outcome of living kidney donors. Methods: We obtained the data of 456 kidney donors registered to the Korean Organ Transplantation Registry from 2014 to 2016. The estimated glomerular filtration rate (eGFR) changes according to the development of incident chronic kidney disease (CKD) and factors related to CKD were analysed. CKD was defined as an eGFR <60 ml/min/1.73 m 2 or the presence of proteinuria or albuminuria. The change in eGFR over time was analysed using a linear mixed model. Results: At 2 years after kidney donation, 21.7% of the donors (99/456) developed CKD. Annual eGFR changes after nephrectomy were 2.2 ml/min/1.73 m 2 /year in donors without CKD, and − 0.4 ml/min/1.73 m 2 /year in donors with CKD. Higher systolic blood pressure was associated with higher risk of CKD (odds ratio [OR] 1.322 per 10 mmHg increment, 95% confidence interval [CI] 1.036–1.686, p = .025). Higher pre‐donation eGFR (OR 0.906 per 1 ml/min/1.73 m 2 increment, 95% CI 0.876–0.936, p < .001) and higher ratio of eGFR at discharge to pre‐donation (OR 0.603 per 0.1 increment, 95% CI 0.426–0.849, p = .004) were related to lower risk of CKD. Conclusion: Kidney donors without incident CKD at 2 years after donation showed gradual increases in eGFR, whereas donors with CKD had relatively constant eGFR. A low ratio of eGFR at discharge after nephrectomy to baseline was a risk factor of CKD. SUMMARY AT A GLANCE: A population cohort study of live donors registered in the Korean Organ Transplant Registry showing that over 1 in 5 live‐donors developed chronic kidney disease at 2‐years post‐donation, and had exhibited decline in eGFR over time. The authors also showed that higher systolic blood pressure was associated with the development of chronic kidney disease suggesting that close long‐term follow‐up of these donors are required.